Efektivitas Media Pop-Up Book Terhadap Hasil Belajar Pendidikan Pancasila Kelas V Sekolah Dasar - Lusy Saskia Farmadani; Emy Yunita Rahma Pratiwi (IJPSE Indonesian Journal of Primary Science Education, 2026)
The low learning outcomes of fifth-grade students in Pancasila Education at SDN Sidokerto 2 Mojowanro Jombang indicate the need for innovation in the instructional process learning activities that are predominantly lecture-basedtend to limit student participation, resulting in suboptimal understanding of the topic of sosial norms. One alternative strategy to echance students’ engagement and comprehension is the use of interactive visual learning media, such as a pop-up book. This study aimed to analyze the effectiveness of pop-up book media in improving elementary students’ learning outcomes. A pre-experimental research design with a one-group pretest-posttest approach was employed the participants consisted of 14 students selected using a saturated sampling technique, data were collected through a pretest administered before the implementation of the learning media and a posttest conducted after the intervention. Priorto hypothesis testing a normality test was perfomed to determine the appropriate statistical analysis. If the data were not normally distributed, the non parametric Wilcoxon tets was applied signification difference between pretestand posttest scores (sig.(2- tailed) = 0,001, α = 0,05) indicatinf that the use of pop-up book media had positive and significant effect on student’ learning outcomes. These findings suggest that interactive visual learning media can serve as aneffective instructional strategy to improve the quality oc civic education leaning in elementary schools.